Analisis Kinerja Reksa Dana Saham Dengan Metode Raw Return, Sharpe, Treynor, Jensen dan Sortino - Simforianus Simforianus; Yanthi Hutagaol (Journal of Applied Finance & Accounting, 2008)
Mutual Fund (Reksa Dana) can be used as one of the investment alternatives besides personal saving, time deposit, shares and bond. Mutual fund is an investment that has a form as a collective contract investment and managed by the profesionals. From various mutual funds in Indonesia, the investor should choose the mutual fund that they want to invest in. The problem is the type of indicators that the investor can use to choose the mutual funds. The writer did research with 16 equity-based mutual funds in Indonesia with the period from December 31, 2002 to December 31, 2007. Firstly, the writer measures all mutual funds according to their performance, which is based on raw return, Sharpe, Treynor, Jensen and Sortino. Mutual funds with above average performance are considered as superior mutual funds. Afterwards, whether there is any consistency in the performance is checked by using probabilistic method and Chi Squared test. Then, ranking will be made started with the best to the worst mutual funds. The candidates for the best mutual funds are the mutual funds that achieve the superior level at least three times during the six years of the research period. The best mutual fund is the mutual fund which obtains the highest rank according to the five methods above. Probabilistic method indicates a high consistency level with an average of 71.50%. This result is supported by the chi squared test, where the hyphotesis that stated that there is a consistency between mutual fund performances can be proven. The final result is the rank of equity-based mutual funds in Indonesia. The following is the rank of the mutual funds with superior performance: Fortis Pesona, Schroder Prestasi Plus, Dana Reksa Mawar, Fortis Ekuitas, Trim Kapital, Panin Dana Maksima, Si Dana Saham, Rencana Cerdas dan Bahana Dana Prima.